تقويم معالجة الغمش بتفاوت أسواء الانكسار بالنظّارات (خبرة مشفى الأسد الجامعي في اللّاذقية بين عامي2013-2014) - سليمان يوسف; علي سندس; ضعون تيماء (Latakia University Journal -Medical Sciences Series, 2016)
الهدف: تقييم فعالية تصحيح سوء الانكسار فقط في علاج الغمش الناجم عن تفاوت سوء الانكسار بين العينين غير المعالج سابقاً. المرضى والطّرائق :قمنا في مشفى الأسد الجامعي في اللاذقية وخلال الفترة الممتدّة كانون الأول 2013 وحتّى كانون الأول 2014 بدراسة مرضى الغمش الناجم عن تفاوت خلل الانكسار بين العينين المراجعين للعيادة العينية وتمّت معالجته بوصف التصحيح البصري المناسب لخلل الانكسار ومتابعة التحسّن في القدرة البصريّة كلّ شهر لمدّة أربعة أشهر من وصف التصحيح. شملت دراستنا 46 مريض تراوحت أعمارهم بين 4-12 سنة ممن لديهم غمش ناجم عن تفاوت خلل الانكسار بين العينين غير المعالج سابقا حيث قمنا بشلّ المطابقة باستخدام سيكلوبنتولات 1% وإعطاء التصحيح البصري المناسب لكلّ حالة. النتيجة : أظهرت دراستنا المحليّة أنّ 28.26% من المرضى حقّقوا نتائج جيّدة ( فرق الحدة البصرية بين العينين أقلّ أو يساوي سطر واحد وهي النتيجة المرجوّة من الدراسة ) و% 71.74 من المرضى مازال فرق الحدة البصرية بين العينين أكبر أو يساوي سطرين على الرغم من بعض التحسّن خلال المتابعة , وتمّت دراسة علاقة تحسّن الحدّة البصرية وزوال الغمش مع القدرة البصرية البدئية للعين الغمشاء (شدة الغمش ) والعمر حيث وجدنا أنّ كلّ المرضى الذين حقّقوا هدف الدراسة كانت قدرتهم البصرية البدئية بين ال 0.3-0.5 و11 مريض من أصل 13 كانت أعمارهم بين ال 4-7 سنوات. الخلاصة : تصحيح سوء الانكسار لوحده ممكن أن يؤدّي لتحسّن ال VA في عدد من الحالات وأدّى لزوال الغمش في ربع مرضى تفاوت سوء الانكسار غير المعالج . Purposes: Studying the effectiveness of refractive correction alone for the treatment of untreated anisometropic amblyopia in children . Patients and methods: We have a study in-Alssad University Hospital in Lattakia during the period December 2013 until December 2014 of patients with anisometropic amblyopia caused by uneven ametropia between eyes at the clinic and has been treated as an appropriate visual correction of ametropia and follow up on improvement in the visual ability of each month for a period of four months from the description of the refractive correction Our study included 46 patients aged between 4-12 years who have anisometropic amblyopia previously untreated eyes where we have to paralyze the corresponding using cyclopntolat1% and give the appropriate optical correction for each case. Results: the local study has shown that 28.26% of the patients achieved results good (visual acuity difference between eyes less or equal to one line which is the desired outcome of the study) and 71.74% of the patients still visual acuity more or equal to two lines despite some improvement during follow-up and we found a relationship between the baseline VA of amplyopic eye, age and the improvement and Resolution of amblyopia , all the patient who achieve the goal of our study . Conclusion : Refractive correction alone improves VA in many cases and results in resolution of amblyopia in one quarter of patients with untreated anisometropic amblyopia.